2010
DOI: 10.1038/nchem.597
|View full text |Cite
|
Sign up to set email alerts
|

A ‘Texas-sized’ molecular box that forms an anion-induced supramolecular necklace

Abstract: The 'blue box' (cyclobis(paraquat-p-phenylene) or CBPQT(4+)), developed by Stoddart and colleagues, forms effective charge transfer complexes with a variety of electron-rich species and has been used to support the formation of a wide range of interlocked structures. However, little effort seems to have been devoted to generalizing the blue box concept. We describe a new flexible tetracationic macrocycle-a 'Texas-sized' molecular box. This positively charged receptor is capable of binding the mono-terephthalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
154
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 279 publications
(159 citation statements)
references
References 49 publications
2
154
0
3
Order By: Relevance
“…Compound H 4 -2A C H T U N G T R E N N U N G (PF 6 ) 4 was initially developed as a molecular box that forms an anion-induced supramolecular necklace, [21] but also appears as a suitable precursor for the preparation of a cyclic tetracarbene ligand.…”
Section: The Major Isomer Was Crystallized As Syn-[ag 2 (1) 2 ]-A C Hmentioning
confidence: 99%
“…Compound H 4 -2A C H T U N G T R E N N U N G (PF 6 ) 4 was initially developed as a molecular box that forms an anion-induced supramolecular necklace, [21] but also appears as a suitable precursor for the preparation of a cyclic tetracarbene ligand.…”
Section: The Major Isomer Was Crystallized As Syn-[ag 2 (1) 2 ]-A C Hmentioning
confidence: 99%
“…62 The authors have previously reported that macrocycle 100 can bind terephthalate dianion 101 on the outside of the macrocycle. 63 Alternatively, when receptor 100 is exposed to the larger dianion 102 a pseudorotaxane is formed with a 2 : 3 host : guest stoichiometry (pseudodimeric species of the pseudorotaxane), as confirmed by 1 H NMR titrations, NOESY NMR and Job plot analysis in DMSO-d 6 and ESI-MS. Furthermore, the addition of related dianion 103 to 100 results in the formation of a pure 1 : 1 pseudorotaxane, as confirmed by 1 H NMR titrations and NOESY NMR experiments.…”
Section: Self-assembled and Anion Templated Molecular Architecturesmentioning
confidence: 99%
“…The properties of these triazolophanes have been recently review by Flood and co-workers. 43 In 2011, this research group also studied a variety of chloride : triazolophane complexes with varying degrees of conformational freedom (62)(63)(64) to verify the importance of structural rigidity as a pre-organisation factor paying the enthalpic cost of bringing together the electropositive CH hydrogen bond donor groups in the triazolophanes. 44 Computational studies were supplemented by 1 H NMR titrations to calculate the binding affinities and preparation free energies (the energy difference between the observed and ideal binding energies) for three triazolophanes (Scheme 7): a ''strongly'' preorganised macrocycle (62), a ''partially'' preorganised macrocycle (63) and a ''poorly'' preorganised macrocycle (64).…”
Section: Anion Receptors Containing Ch Hydrogen Bond Donorsmentioning
confidence: 99%
“…[34,35] These ligands offer the possibility of chelation by binding to the metal centre through both the carbenic carbon and pyridyl nitrogen, with ligand 1i having two potential NHC donors. In the solid-state structures of imidazolium salts 1f, 1g and 1i, the pyridyl and imidazolium rings lie almost coplanar, which acts to increase -overlap between the two ( Figure 7).…”
Section: A Potential Strategy For the Stabilisation And Examination Omentioning
confidence: 99%